Randomized controlled trials of multi-sectoral programs: Lessons from development research - Quisumbing, Agnes R.; Ahmed, Akhter; Gilligan, Daniel O.; Hoddinott, John F.; Kumar, Neha; Leroy, Jef L.; Menon, Purnima; Olney, Deanna K.; Roy, Shalini; Ruel, Marie T. (Elsevier, 2020)
Development is a multi-faceted process; achieving development goals thus requires a multi-sectoral approach. For over two decades, our research group of economists and nutritionists has designed and implemented randomized trials to assess the effectiveness of multisectoral programs in improving nutrition, food security, and other measures of well-being, largely at the request of developing country governments, development partners, and non-governmental organizations. Our approach addresses three perceived pitfalls of RCTs: the “black box” nature of RCTs, limited external validity, and challenges in translation of results to impacts at scale. We address these concerns by identifying and assessing programmatic pathways to impact with quantitative and qualitative methods; studying similar programs implemented by different organizations across various settings; and working closely with implementing partners in the design, research, and dissemination processes to inform adaptation and scale-up of programs and policies.